Chalcogenide solution-mediated activation protocol for scalable and ultrafast synthesis of single-crystalline 1-D copper sulfide for supercapacitors. Issue 6 (25th January 2019) - Hong, John; Kim, Byung-Sung; Yang, Seungmo; Jang, A-Rang; Lee, Young-Woo; Pak, Sangyeon; Lee, Sanghyo; Cho, Yuljae; Kang, Dongwoo; Shin, Hyeon Suk; Hong, Jin Pyo; Morris, Stephen M.; et al.
Abstract : One-dimensional Cu2 S nanostructures via a facile and room-temperature sulfur activation for supercapacitors. Abstract : Traditional synthetic routes for transition metal sulfides typically involve solution and thermal-based processes to exploit their favorable pseudo-capacitive properties. However, there is a practical need to develop alternative processes to fabricate metal sulfide electrodes because of the time-consuming processes (>12 h), additional heat-treatment to active reactants, relatively high post-heat-treatment temperature (200–400 °C) and non-scalable nature of existing synthetic routes. Herein, utilizing a solution-based sulfur precursor, one-dimensional single-crystalline Cu2 S nanostructures have been successfully prepared via a solution-based direct synthesis process within 10 min at room temperature without the need for thermal treatment steps. The fabricated electrode exhibits a capacitance of 750 mF cm −2 at a current density of 2 mA cm −2 . Moreover, the rate capacitance is maintained at about 82.3% as the current density is increased to 40 mA cm −2, and the capacity retains 90.5% of the initial value after 20 000 cycles. Importantly, as this method involves a solution-based formulation it is compatible with roll-to-roll processes, which is promising for mass and scalable production of the electrodes. The synthetic method ensures a facile and efficient approach to fabricating scalable one-dimensional single crystalline Cu2 S nanostructures, highlighting the uniqueness of the solution-based sulfur activation method.